Education: Misunderstood Purpose and Failed Solutions - Paul A. Wagner; Lilian Benavente-McEnery (Arizona State University, 2015)
There is so much quarrelling surrounding education today it seems people have lost sense of what needs arguing about, where there is a need for more research and where there are grounds for general agreement. Grounds now exist for shared agreement on matters of educational purpose. Moreover, there has in fact been much agreement on such matters over the years. With one flag to salute, people in education should be in a much better position to strategize on those tactics most likely to achieve our common pragmatically issued goals.